CESifo World Economic Survey May 2005 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2005)
World Economic Climate: World Economic Climate remains in a cooling-down phase - Economic Expectations: Assessment of current economic situation and expactations both somewhat weakened but still positive - Inflation: Stable rate expected - Interest Rates: Trend of moderately rising rates expected to continue - Currencies: Euro still seen as clearly overvalued - Special Topic: World Trade Negotiations
Keywords: 330